An ANALYSIS OF SOCIAL SCIENCE EDUCATION THROUGH AN ENVIRONMENTAL APPROACH AS A LEARNING RESOURCE - Prasetya, Sukma Perdana; Sarmini, Sarmini; Zain, Ita Mardiani; Artono, Artono; Sadewo, FX Sri; Mahat, Hanifah; Hidayati, Armawati (Universitas Negeri Surabaya, 2022)
This study aims to: 1) Assess social sciences learning practices at the SMP level. in Maospati District, Madiun Regency in utilizing the surrounding environment as a social sciences learning resource, and (2) analyzing teachers' insights and abilities in developing environmentally sound learning as a learning resource in order to improve ecopedagogy abilities. The object of study in this research is all dimensions of social sciences learning at SMPN 1 in Maospati District, which consists of curriculum, textbooks, learning models, learning resources, learning facilities and infrastructure, and the carrying capacity of the learning environment. The data collected in this study is in the form of qualitative data. Data processing uses qualitative analysis. The results of the first year's research showed: (1) Empowerment of environmental elements around Maospati District was not optimal for teachers in developing materials and choosing social sciences learning resources, and (2) Lack of insight and ability of teachers in developing ecopedagogy learning on empowering elements the surrounding environment is important as a social sciences learning resource. Keywords : IPS learning; environment, ecopedagogy